THE AESTHETIC MOVEMENT: OSCAR WILDE AND THE ART FOR ART’S SAKE PHILOSOPHY (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2025)
This article discusses the Aesthetic Movement of the late nineteenth century, focusing on Oscar Wilde as its central representative. The study analyzes how Wilde’s works express the “Art for Art’s Sake” philosophy, which sought to liberate art from moral, political, and utilitarian functions. Through close reading of Wilde’s The Picture of Dorian Gray and The Importance of Being Earnest, the paper argues that Wilde viewed beauty and artistic experience as the highest forms of truth. The analysis also reveals how his aesthetic ideals challenged Victorian moralism and laid the foundation for modernist and postmodernist artistic freedom.